Berberine Inhibition of Fibrogenesis in a Rat Model of Liver Fibrosis and in Hepatic Stellate Cells - Wang, Ning (Evid Based Complement Alternat Med, 2016)
Aim. To examine the effect of berberine (BBR) on liver fibrosis and its possible mechanisms through direct effects on hepatic stellate cells (HSC). Methods. The antifibrotic effect of BBR was determined in a rat model of bile duct ligation- (BDL-) induced liver fibrosis. Multiple cellular and molecular approaches were introduced to examine the effects of BBR on HSC. Results. BBR potently inhibited hepatic fibrosis induced by BDL in rats. It exhibited cytotoxicity to activated HSC at doses nontoxic to hepatocytes. High doses of BBR induced apoptosis of activated HSC, which was mediated by loss of mitochondrial membrane potential and Bcl-2/Bax imbalance. Low doses of BBR suppressed activation of HSC as evidenced by the inhibition of α-smooth muscle actin (α-SMA) expression and cell motility. BBR did not affect Smad2/3 phosphorylation but significantly activated 5′ AMP-activated protein kinase (AMPK) signalling, which was responsible for the transcriptional inhibition by BBR of profibrogenic factors α-SMA and collagen in HSC. Conclusion. BBR is a promising agent for treating liver fibrosis through multiple mechanisms, at least partially by directly targeting HSC and by inhibiting the AMPK pathway. Its value as an antifibrotic drug in patients with liver disease deserves further investigation.